Modelling challenges to unlock the power of phototrophic systems for wastewater valorization - Casagli, Francesca; Turolla, Andrea; Batstone, Damien J; Capson-Tojo, Gabriel; Ficara, Elena; García, Joan; Gonzalez-Flo, Eva; Laurent, Julien; Lorenz, Tatjana; Pierrelée, Michaël; Plósz, Benedek Gy; Da Silva, Gustavo Henrique Ribero [UNESP]; et al. (Elsevier, 2025)
Phototrophic microorganisms are gaining prominence for their dual role in wastewater treatment and resource recovery, converting wastewater into valuable bioproducts. However, their effective deployment needs robust modelling frameworks capable of predicting performance across complex, real-world scenarios. Despite significant advances, key challenges hinder the development and application of such models.